2007
DOI: 10.1111/j.1365-2427.2007.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter breakdown budgets in streams of various trophic status: effects of dissolved inorganic nutrients on microorganisms and invertebrates

Abstract: 1. We investigated the effect of trophic status on the organic matter budget in freshwater ecosystems. During leaf litter breakdown, the relative contribution of the functional groups and the quantity/quality of organic matter available to higher trophic levels are expected to be modified by the anthropogenic release of nutrients. 2. Carbon budgets were established during the breakdown of alder leaves enclosed in coarse mesh bags and submerged in six streams: two oligotrophic, one mesotrophic, two eutrophic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 46 publications
7
68
2
Order By: Relevance
“…Such data help clarify the functional role of microbial assemblages (bacteria and fungi) and consumers (e.g., invertebrates) in organic matter processing (Hieber and Gessner 2002) and could provide unique insights into the potential effects of eutrophication on detrital carbon and nutrient flow pathways in ecosystems (Baldy et al 2007;Suberkropp et al 2010). Data collected in the present study allows the construction of a partial budget to assess the contribution of fungal decomposers to overall leaf carbon loss in T. angustifolia.…”
Section: Discussionmentioning
confidence: 99%
“…Such data help clarify the functional role of microbial assemblages (bacteria and fungi) and consumers (e.g., invertebrates) in organic matter processing (Hieber and Gessner 2002) and could provide unique insights into the potential effects of eutrophication on detrital carbon and nutrient flow pathways in ecosystems (Baldy et al 2007;Suberkropp et al 2010). Data collected in the present study allows the construction of a partial budget to assess the contribution of fungal decomposers to overall leaf carbon loss in T. angustifolia.…”
Section: Discussionmentioning
confidence: 99%
“…4H). These estimates of fungal importance in litter decomposition do not include fungus-mediated losses of plant carbon as dissolved organic carbon and fine particulate organic carbon, which can be comparable to losses of plant C due to respiration (3). A considerable portion of allochthonous litter input may be also lost from a stream reach due to downstream transport and other breakdown factors, such as abiotic leaching, mechanical fragmentation, and invertebrate feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrients can stimulate bacterial and fungal growth, which can increase detrital food quality (Meyer and Johnson 1983, Arsuffi and Suberkropp 1989, Stelzer et al 2003. Baldy et al (2007) found that microbial biomass and CO 2 production on leaf litter increased along a dissolved P gradient and then reached a plateau between 0.02 and 0.04 mg/L soluble reactive P (SRP). Rosemond et al (2002) also found that the half-saturation constant for litter decay across 16 tropical stream sites with differing SRP concentrations was between 0.007 and 0.013 mg/L SRP.…”
Section: Discussionmentioning
confidence: 99%